Multiple Intelligences In The Perspective Of Islamic Education: A Systematic Literature Review - Samsudin, Rohman; Ahmad Daqiqi Syahrulloh; Faikatul Jannah; Eti Sumiati; Alfian Fahmi Majid; Siti Roudhotul Jannah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the concept, implementation, and challenges of applying Multiple Intelligences within the perspective of Islamic education using a Systematic Literature Review (SLR) approach. The research method employed is a systematic literature review by collecting, selecting, and analyzing various scientific articles relevant to the research topic. Data sources were obtained from national journals published between 2022 and 2026. The analysis process was carried out through several stages, including article identification, selection based on inclusion and exclusion criteria, and synthesis of research findings relevant to the study theme. The results indicate that the concept of Multiple Intelligences aligns with the principles of Islamic education, which emphasize the holistic development of human potential, including intellectual, spiritual, social, and moral aspects. The implementation of this concept in Islamic education can be carried out through various learning strategies such as discussions, project-based learning, religious practices, and the use of diverse instructional media. This approach has been proven to enhance student engagement, learning creativity, and understanding of Islamic values. However, the implementation of Multiple Intelligences also faces several challenges, including limited teacher understanding of the concept, inadequate learning facilities and infrastructure, and evaluation systems that still focus primarily on cognitive aspects. Therefore, efforts are needed to improve teacher competence and institutional support in developing learning strategies based on Multiple Intelligences. In conclusion, this approach is expected to contribute to improving the quality of Islamic education in a more holistic and student-centered manner.